Eleven-Year Report on a Predoctoral Implant Dentistry Program - Ahmad Maalhagh-Fard, DDS, MS1 & Arthur Nimmo, DDS2 (Journal of Prosthodontics, 2008)
An elective program on implant dentistry was started in the summer of 1994 at the University of Detroit Mercy School of Dentistry (UDM).